2013
DOI: 10.1088/0965-0393/21/7/075010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics modeling and simulation of void growth in two dimensions

Abstract: The mechanisms of growth of a circular void by plastic deformation were studied by means of molecular dynamics in two dimensions (2D). While previous molecular dynamics (MD) simulations in three dimensions (3D) have been limited to small voids (up to s«10nm in radius), this strategy allows us to study the behavior of voids of up to 100 nm in radius. MD simulations showed that plastic deformation was triggered by the nucleation of dislocations at the atomic steps of the void surface in the whole range of void s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 58 publications
(109 reference statements)
3
20
0
Order By: Relevance
“…In this section, we perform MD simulations to explore the effects of certain variables including the temperature T , the strain rateε, the loading direction ings agree with earlier MD work by Chang et al [18]. In the remainder of this paper, a constant temperature of 10 K is employed.…”
Section: Effects Of Cerntain Variables (T ε β and F 0 )mentioning
confidence: 85%
See 1 more Smart Citation
“…In this section, we perform MD simulations to explore the effects of certain variables including the temperature T , the strain rateε, the loading direction ings agree with earlier MD work by Chang et al [18]. In the remainder of this paper, a constant temperature of 10 K is employed.…”
Section: Effects Of Cerntain Variables (T ε β and F 0 )mentioning
confidence: 85%
“…In recent years, numerous researchers have employed MD simulations to investigate the issue of nanovoid growth. Traiviratana et al [16] found that the emission of dislocation loops is the primary mechanism of void growth in face-centered cubic (FCC) Cu when the specimen is subject to tensile uniaxial strains; Potirniche et al [17] revealed a pronounced effect of the specimen size on dislocation formation from voids and plastic flow in FCC Ni; Chang et al [18] showed that with an increasing temperature, the yield stress decreases while the void growth rate remains invariant; Bringa et al [19] studied the effect of the loading orientation in the void behavior in Cu, and their results exhibited a complex coupling of void growth, GB debonding, and partial dislocation emission into grains in nanocrystals; Seppälä et al [20] quantified the effect of stress triaxiality on the void growth in Cu; Deng et al [15] uncovered a strong configurational effect on the coalescence of voids in Cu under a shock loading. Using the quasicontinuum method, Marian et al [21] and Ponga et al [22] studied the nanovoid deformation in FCC Al under tension and simple shear, identifying a transitional strain rate between a quasistatic and a dynamic regime.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the micro-mechanisms and kinetics of the above processes is critical to predicting damage evolution in a given microstructure, as well as establishing guidelines for the design of damage-resistant microstructures. As a result, many efforts have been devoted to understanding damage nucleation and evolution under such loading conditions [1,2]. For example.…”
Section: Introductionmentioning
confidence: 99%
“…A benefit of this ''2D'' simulation geometry is that it allows us to have a clear view of the material transport in the high strain regime when the primary growth of the voids prevails. Chang et al [35] suggested that the yield stress simulated by MD in 2D is very close to that in 3D at 0 K. Nevertheless, the extension toward a cubic 3D simulation geometry would be helpful in that it provides spacing space in the third direction for the motion of dislocations and the formation of complete dislocation loops. Some dislocation mechanisms like the prismatic loop emission induced by inclusions are more physically suitable for 3D simulations.…”
Section: Introductionmentioning
confidence: 99%